Spatiotemporal variation in fish species distribution and abundance in the Vaishav stream, Kashmir Himalaya–India - Gowhar Rashid; Rahul Singh; Abhinav Kumar; Prabhu Paramasivam (PLoS ONE, 2025)
Exploring the intricate dynamics of aquatic ecosystems present study investigates the spatio-temporal variations in the ecological parameters of the fish community within the Vaishav stream, Kashmir Himalayas. Monthly field investigations were conducted at three distinct sites (SI, SII & SIII) throughout the four seasons (winter, spring, summer, autumn) from November 2019 to October 2020. The findings encompass a total of 630 specimens belonging to 11 fish species, three orders Cypriniformes, Siluriforms and Salmoniformes and four families including Cyprinidae, Nemachelidae, Siluridae and Salmonidae were reported from the study sites. Among collected specimens, Cypriniformes were dominant with nine species followed by order Siluriformes and Salmoniformes with one species each. Out of eleven fish species, six fish species belongs to family Cyprinidae, three to Nemachelidae, one to Siluridae and Salmonidae each. The analysis, employing non-metric multidimensional scaling (NMDS), Principal component analysis (PCA), Analysis of similarity (ANOSIM) and Per-mutational multivariate analysis of variance (PERMANOVA) on fish abundance data highlighted significant differences among the various sites but not across seasons. The results unveil a diverse occurrence and distribution pattern of fishes from upstream to downstream. Furthermore, diversity metrics confirm higher diversity index values downstream, indicating a more conducive environment for fish survival. Jaccard’s index reveals greater similarity in fish fauna between site-II and site-III than site-I and site-III in terms of overlap of fish species composition. The study concludes that anthropogenic activities in the stream catchment area have led to a reduction in fish diversity and abundance, with landscape features significantly influencing fish abundance in this unique Himalayan ecosystem.